Water, sanitation, and hygiene (WASH) in healthcare facilities of 14 low- and middle-income countries: to what extent is WASH implemented and what are the ‘drivers’ of improvement in their service levels? - Laura Kmentt (IWA Publishing, 2021)
Prevention and control of healthcare-associated infections through the provision of water, sanitation, and hygiene (WASH) in healthcare facilities (HCF) is inadequate in low- and middle-income countries (LMICs), resulting in high patient morbidity and mortality, additional costs, and increased risk of antibiotic resistance. There is little evidence describing factors leading to improved WASH conditions in LMICs. We aim to identify the extent to which WASH is implemented in HCFs in LMICs and understand the ‘drivers’ of improvement in their service levels. WASH service levels in 14 LMICs were descriptively analysed, and potential drivers of service-level differences were explored using univariable and multivariable mixed-model logistic regression analyses. Descriptive analysis showed a lack of adequate water quality, sanitation, hand, and environmental hygiene, and waste disposal. We found that the presence of infection prevention and control protocols (IPCPs), having an IPC/WASH focal person at the facility, and conducting WASH training for staff were associated with higher levels of WASH services. This study demonstrates a lack of basic WASH services in HCF in LMICs. We show that there are potential interventions, such as implementing IPCPs, identifying WASH leaders in HCF, and conducting training that may lead to service improvements. HIGHLIGHTS Infection prevention and control protocols, a facility WASH focal person, and WASH training for staff could improve WASH service levels at facilities.; Managerial interventions could be just as vital as hardware interventions in improving WASH service levels at facilities.; The SDG WASH in healthcare facility targets are not met in most LMICs.; Research into the policy context for local capacity building is required.;